(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The balance between translation precision and speed is influenced by rRNA changes, although the exact processes involved are still unknown. By studying alterations in ribosomal RNA, it may be possible to understand the functions of different bacteria species, even if they are taxonomically distant. The methyltransferases responsible for these alterations play a role in adjusting ribosomal function, especially during stressful situations. In the case of Escherichia coli, two methyltransferases (RsmI and RsmH) have been found to be responsible for cytidine dimethylation in the ribosome’s decoding site. However, the physiological implications of these rRNA alterations are not yet clear.Using a silkworm infection model. rsmI & rsmH have been discovered by research to be novel s. aureus virulence genes. These genes cause specific methylations of the S. aureus 16S rRNA, resulting in changes in the bacterium’s susceptibility to oxidative stress and its virulence in silkwormsThe loss of virulence results from the elimination of both rsmI or rsmH. While under stress from oxidation, a double-knockout strain exhibits decreased translated accuracy. Additionally, the inactivation of rlmQ, which affects methylation at a different location (G2601) in S. aureus rRNA, has a significant impact on the bacterium’s proliferation, cytotoxicity, and biofilm formation.To further understand the relationship between translation, virulence, and rRNA changes in dangerous gram-positive bacteria, researchers injected N-acetyl-l-cysteine, a scavenger of free radicals, which restored the ability of the double-knockout strain to kill silkworms. Researchers have discovered that the pathogenicity of Staphylococcus aureus is influenced by RNA ribosomal methyltransferases. They conducted a study in which they administered N-acetyl-l-cysteine, a free radical scavenger, into a double knockout strain of the bacteria Staphylococcus aureus. The injection had restored the strain’s capacity to kill silkworms. Based on these data, it can be concluded that the methyl modifications of cytidine at site [1412] in the 16S r RNA contribute to the pathogenesis of Staphylococcus auras, especially through the organism’s response to oxidative stress